2021
DOI: 10.1038/s41371-020-00478-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, awareness, treatment and control of young-onset hypertension in Malaysia, 2006–2015

Abstract: The continuous presence of elevated blood pressure (BP) when young is a strong predictor of future cardiovascular risk. This study aimed to elucidate the prevalence, awareness, treatment and control of young-onset hypertension (YOH) in Malaysia during the period 2006–2015. Data on respondents aged 18–39 diagnosed with YOH according to the 7th Joint National Committee Report (USA) were extracted from three National Health and Morbidity Surveys (2006, 2011, and 2015). The prevalence of YOH remained stable: 17.7%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…2 ; and Online Resource, Supplementary Table S4 for the HDI ranking of Asian countries). Where trends over time were available, they showed that BP control rates are improving [ 137 , 142 , 143 , 157 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 ; and Online Resource, Supplementary Table S4 for the HDI ranking of Asian countries). Where trends over time were available, they showed that BP control rates are improving [ 137 , 142 , 143 , 157 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Not all these factors have been studied, but our search did identify some studies showing better BP control among certain subgroups of patients (Table 5 ). Nonmodifiable factors that influenced BP control included sex/gender [ 137 , 139 141 , 145 , 146 , 149 , 150 , 153 , 158 ], ethnicity [ 137 , 144 , 145 , 154 ], age [ 137 , 141 , 142 , 144 , 149 , 154 , 158 ], family history [ 154 ], time since diagnosis [ 139 ] and the presence of cardiovascular disease [ 159 ] or comorbidities [ 143 , 145 ]. Socio-economic factors that affected BP control included living in an urban versus rural area [ 137 , 138 , 146 , 154 ], household income [ 139 , 141 , 144 146 , 149 , 150 ], education level [ 141 , 144 , 145 , 150 , 154 ], marital status [ 145 , 146 , 149 , 150 ], employment status [ 144 , 146 ] and health insurance [ 139 ].…”
Section: Resultsmentioning
confidence: 99%
“…The age of 18 to 64 years is the most productive age for working and maintaining their family's needs [7]. Unfortunately, younger age adults were associated with low awareness of CVD risk as found by previous local studies[8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…The age range of 18 to 64 years is the most productive age for working and maintaining their family's needs [7]. Unfortunately, younger adults were associated with low awareness of CVD risk, as found by previous local studies [8,9].…”
Section: Introductionmentioning
confidence: 99%